Retrofitting building fire service water tanks as chilled water storage for power demand limiting. (January 2017) - Yan, Chengchu; Wang, Shengwei; Fan, Cheng; Xiao, Fu
Peak demand cost usually contributes a large proportion of the total electricity bills in buildings. Using existing building facilities for power demand limiting has been verified as effective measures to reduce monthly peak demands and associated costs. Fire service water tanks exist in most commercial buildings. This paper presents a comprehensive study on how to effectively retrofit existing building fire service water tanks as chilled water storage for power demand limiting. Important technical and economic factors that may affect the implementation of the proposed retrofitting are addressed. Two retrofitting schemes, i.e. a small ΔT (storage temperature difference) scheme and a large ΔT scheme are proposed for integrating the chilled water storage system into an existing all-air system and an existing air-water air conditioning system, respectively. Two optimal demand limiting control strategies, i.e. time-based control and demand-based control, are proposed for maximizing the monthly peak demand reduction of buildings with regular and variable peak occurring time, respectively. The cost-effectiveness of different retrofitting schemes in three real buildings in Hong Kong is analysed. Results show that substantial cost savings can be achieved with short payback periods (0.7–2.6 years) for the retrofits in these three buildings. Practical application : This paper presents a techno-economic analysis on retrofitting existing building fire service water tanks as chilled water storage for power demand limiting and operational cost saving. The proposed retrofitting schemes and demand limiting control strategies enable chilled water storage systems to be readily applied to most existing buildings. Building owners can benefit from the peak demand cost saving as the monthly peak demand can be significantly reduced by using chilled water storage. The extra costs involved in tank retrofits and system integrations can be paid back within three years.